Results in the Latin America and Caribbean Region 2019, Volume 13 - World Bank (World Bank, Washington, DC, 2022)
The World Bank’s work in Latin America and the Caribbean has one overriding priority: better lives for its people. All of us working at the Bank dream of a region where people can work and prosper. Where the next generation will live better than the current one; where kids get quality education and mothers quality health care; where individual circumstances at birth such as gender or being born in a rural area do not determine the chances of success in life; and where governments meet the demands of their population for transparency. We all dream of a region where poverty has been eliminated and the development process leads to shared prosperity.